A Doubly Bridged Bis(phenylethynyl)benzene: Different from a Twisted Tolan. Issue 71 (24th November 2020) - Hodecker, Manuel; Kozhemyakin, Yury; Weigold, Svenja; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F.
Abstract: The synthesis of a doubly bridged 1, 4‐bis(phenylethynyl)benzene is reported. The target displays photophysical properties, distinctly different from that of its congeners, the singly bridged tolans. Quantum‐chemical calculations suggest a lack of planarization of the bridged bis(phenylethynyl)benzene in the first excited state. Abstract : Two are better than one? This work reports the synthesis and properties of a twofold bridged bis(phenylethynyl)benzene, which, due to its two tethers, does not planarize in the excited state in contrast to its mono‐bridged tolan counterpart.